Ketepatan Smash Dalam Permainan Bulutangkis: Kontribusi Faktor Psikologis Atlet - Surya Muharram; Irsan Kahar; Nur Saqinah Galugu (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2022)
Smash in badminton is a blow that is often used and is the mainstay of athletes to turn off the ball and score points, therefore athletes must pay attention to the factors that support the accuracy of the smash. In addition to physical factors, athletes also need to pay attention to psychological factors that support their ability to smash. This research was conducted at PB Spirit Badminton Hall and PB sinar setuju, Palopo city, which aims to determine the contribution of athletes' psychological factors to smash accuracy. This research is a quantitative research, with a correlational design that takes a sample of 50 people and is selected using an accidental sampling technique. The data was collected using an anxiety and self-confidence questionnaire that was distributed using the google form platform, while the accuracy of the smash was measured directly by the researcher with an accuracy test. The collected data was analyzed with the help of SPSS 25.0 for windows. The results showed that the athlete's anxiety and confidence contributed or had a correlation with the level of accuracy of the smash performed by badminton athletes.